Objective Structured Clinical Examinations (OSCE) improved communication skills of student of Pharmacology in Medicine and Podiatry degree. - Bellido-Estévez, Inmaculada; Blanco-Reina, Encarnación; Gómez-Luque, José Aurelio (7th European Congress of Pharmacology (EPHAR-2016), 2016)
Objective Structured Clinical Examinations (OSCE) improved communication skills of student of Pharmacology in Medicine and Podiatry degree. Bellido I, Blanco E, Gomez-Luque A. D. Pharmacology and Clinical Therapeutic. Medicine School. University of Malaga. IBIMA. Malaga, Spain. Objective Structured Clinical Examinations (OSCEs) are versatile multipurpose evaluative tools that can be utilized to assess health care professionals in a clinical setting including communication skills and ability to handle unpredictable patient behavior, which usually are not included in the traditional clinical exam. To designee and perform OSCEs by student is a novelty that really like to the students and may improve their arguing and planning capacities and their communication skills. Aim: To evaluate the impact of designing, developing and presenting Objective Structured Clinical Examinations (OSCE) by student in the communication skills development and in the learning of medicines in Medicine and Podiatry undergraduate students. Methods: A one-year study in which students were invited to voluntarily form groups (4 students maximum). Each group has to design and perform an OSCE (10 min maximum) showing a clinical situation/problem in which medicines’ use was needed. A clinical history, camera, a mobile-phone's video editor, photos, actors, dolls, simulators or whatever they may use was allowed. The job of each group was supervised and helped by a teacher. The students were invited to present their work to the rest of the class. After each OSCE performance the students were encouraged to ask questions if they wanted to do it. After all the OSCEs performances the students voluntarily answered a satisfaction survey. Results: Students of Pharmacology of Medicine degree and Podiatry degree, N=80, 53.75% female, 21±2.3 years old were enrolled. 26 OSCEs showing a clinical situation or clinical problem were made. The average time spent by students in making the OSCE was 21.5±9 h. The percentage of students which were satisfied with this way of presentation of the OSCE was 89.7%. Conclusion: Objective Structured Clinical Examinations (OSCE) designed and performed by student of Pharmacology of the Medicine and Podiatry Degree improved their communication skills.
Abstract congreso
Keywords: Comunicación interpersonal; Objective Structured Clinical Examinations (OSCE); Communication skills Assessment